Social Ties and the Job Search of Recent Immigrants - Deepti Goel; Kevin Lang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
We show that increasing the probability of obtaining a job offer through the network should raise the observed mean wage in jobs found through formal (non-network) channels relative to that in jobs found through the network. This prediction also holds at all percentiles of the observed wage distribution, except the highest and lowest. The largest changes are likely to occur below the median. We test and confirm these implications using a survey of recent immigrants to Canada. We also develop a simple structural model, consistent with the theoretical model, and show that it can replicate the broad patterns in the data. For recent immigrants, our results are consistent with the primary effect of strong networks being to increase the arrival rate of offers rather than to alter the distribution from which offers are drawn.
Keywords: 330